First record of a specialized hygropetricolous cave beetle, genus Croatodirus (Coleoptera: Leiodidae), in Slovenia - Teo Delić (Natura Sloveniae)
The cave hygropetric, an inaccessible subterranean habitat defined by films of water flowing down the cave walls, is renowned for its specialized filter feeding cave beetles. To date, no data on cave hygropetricolous beetles have been known for Slovenia, despite the existence of suitable karst areas. This paper reports on the first finding of a hygropetricolous cave beetle in Slovenia. A single female of a species belonging to the genus Croatodirus was discovered in the cave »Brezno treh src« on the Snežnik Plateau. The geomorphology and climate of the sampling site as well as the biology of hygropetricolous cave beetles are briefly described.